The border region : a geographical study of land utilization - Board, Christopher (Rhodes University, Faculty of Science, Department of Geography, 1961)
From Summary: This is a geographical study of land use in the Eastern Cape Province. The land use pattern, although related closely to the features of the natural environment, is perhaps even more closely related to the spatial variations of the man-made environment, particularly to the disposition of the different racial groups with their different cultures and economies, and to the kaleidoscopic character of the settlement pattern.
Keywords: Land use -- South Africa -- Cape of Good Hope; Vegetation and climate -- South Africa -- Cape of Good Hope; Geology -- South Africa -- Cape of Good Hope; Cape of Good Hope (South Africa) -- Environmental conditions